A General Description of Electronic Texts in Comparison with Other Types of Speech - HOVHANNISYAN, SIRANUSH (Bulletin of Yerevan University B: Philology, 2021)
This article analyses the electronic text as a modern manifestation of the largest unit of language – text. Firstly, text is, in general, characterized as a unit exhibiting complex splitting. On the one hand it is a means of communication, and on the other hand, a personal view of objective reality. Taking this peculiarity into consideration, a distinction is drawn between linguistic and nonlinguistic text types. These text types in turn are subdivided into personal and general types, respectively. Modern type of the text is defined as an expressive example set of linguistic and non-linguistic elements. Further, depending on its nature and functions,electronic text is divided into two groups: a text chat and a text message. The analysis of the latest manifestations of the text (compared to its traditional types) reveals that the electronic text types take an intermediate position between written and oral text types. The article discusses the influence of electronic text on individual speech, spoken languageand, eventually, on language itself. Nowadays, due to the versatility to integrate both linguistic and non-linguistic components, electronic versions of linguistic units are favored over the already stated text types with strictly linguistic structure.
Keywords: written language, oral speech, telecommunication, electronic text, linguistic text, non-linguistic text, text-chat, text-message,non-linguistic component